1990
DOI: 10.1063/1.103177
|View full text |Cite
|
Sign up to set email alerts
|

Blue light-emitting organic electroluminescent devices

Abstract: Organic electroluminescent (EL) devices with multilayered thin-film structures which emitted bright blue light were constructed. Two empirical guides for the selection of blue-emitting materials were established. The keys to obtain the EL cells with high EL efficiency were excellent film-forming capability of an emitter layer and the appropriate combinations of emitter and carrier transport materials for avoiding the formation of exciplexes. In one of our organic electroluminescent devices, blue emission with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
330
0
5

Year Published

1997
1997
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 691 publications
(337 citation statements)
references
References 6 publications
2
330
0
5
Order By: Relevance
“…͓DOI: 10.1063/1.2989133͔ Electroluminescent ͑EL͒ devices based on conjugated polymers continue to be of interest as potential elements for flexible displays. [1][2][3][4] Although encouraging progress has been made in recent years, injection from the electrodes into the luminescent conjugated polymers continues to be a problem. The mismatch between the work function of the metallic electrode ͑cathode͒ and the lowest occupied molecular orbital energy level of the semiconducting polymer controls charge injection into the devices, thereby limiting the device efficiency.…”
mentioning
confidence: 99%
“…͓DOI: 10.1063/1.2989133͔ Electroluminescent ͑EL͒ devices based on conjugated polymers continue to be of interest as potential elements for flexible displays. [1][2][3][4] Although encouraging progress has been made in recent years, injection from the electrodes into the luminescent conjugated polymers continues to be a problem. The mismatch between the work function of the metallic electrode ͑cathode͒ and the lowest occupied molecular orbital energy level of the semiconducting polymer controls charge injection into the devices, thereby limiting the device efficiency.…”
mentioning
confidence: 99%
“…In 1990, it was found that a compound with 1,3,4-oxadiazole is an excellent electron transport material in an organic electroluminescent diode [21]. After this report, the research to use various oxadiazole molecules to obtain high electroluminescence performances strongly increased.…”
Section: Oxadiazoles For Electroluminescencementioning
confidence: 95%
“…Since the first reports of organic electroluminescent (EL) devices in the late 1980s [1][2][3][4], there has been significant interest in the field of organic light-emitting diodes (OLEDs) driven by questions related to fundamental research as well as by proposed industrial applications. An example is solid-state lightning [5][6][7], which holds great promise as an energy-efficient light source.…”
Section: Introductionmentioning
confidence: 99%
“…Another problem related to the issue of a high band gap is the consequence that the lowest unoccupied molecular orbital (LUMO) is close to the vacuum energy level, which reduces the lifetimes of blue OLEDs because the material is susceptible to oxidation. Nevertheless, there are many reports on blue-emitting OLEDs [4,[11][12][13][14][15][16][17][18][19][20] and the optimization of device structure as well as the investigation of new blue emitters is still in progress.…”
Section: Introductionmentioning
confidence: 99%